Closed-Canopy Tropical Forests of Hainan, (China) Are Resilient against Invasive Herbs and Shrubs - Xiaobo Yang (MDPI AG, 2021)
The successful establishment of many plants in tropical forests often depends on species-specific adaptations related to light availability and forest successional stage. Species that are present in early successional stages generally do not occur in later successional stages. In this study, we documented the diversity, distribution, and abundance of terrestrial invasive plants across the (sub)tropical island of Hainan, China, and tested the germination of specific invasive plants in forested environments. In 97 transects positioned randomly across the island, we found nine invasive herb and shrub species were present in all human-modified habitats but not in intact forest interiors. In separate forest-specific transects, we documented a sharp drop in the abundance of invasive plants >5 m into the forest. High numbers of invasive plant seeds germinated from the soil seed bank sampled at the forest edge, but very few seeds germinated from soil sampled any distance into the forest. Finally, in experiments with four focal invasive plant species, overall germination rates were low; and much lower in shaded sites compared to full gap sites. In conclusion, our findings demonstrated that invasive herbs and shrubs do not yet form a serious threat to native species in the closed-canopy forests of Hainan.